PENGARUH KEPERCAYAAN, KEPUASAN DAN RELATIONSHIP VALUE TERHADAP KOMITMEN PADA NASABAH KARTU KREDIT MANDIRI MEDAN - mardiyah irfa (Universitas Sumatera Utara, 2013)
ABSTRACT The purpose of this study are to investigate and analyze the impact of trust, satisfaction and relationship value toward customer commitment in mandiri credit card Medan. The population of this study is the new customers Mandiri Credit Card in 2011, with the amount of 31 524 people. Samples used in this study are Bank Mandiri credit card customers listed in 2011. The sample size in this study was determined using the Slovin formula. Number of samples obtained at 99.68 is rounded up to 100 people. The author used a sample random sampling method. Based on partial test results, it is known a variable relationship value, while the satisfaction variable and the trust variable also have a positive influence on customer commitment Medan Mandiri credit card but not significant. Based on the test results of the determinant coefficient (R), can be seen that the value of the determinant coefficient (R) by 45.6% of commited customers of credit card in Medan Mandiri is jointly influenced by the belief variables, satisfaction and the variable relationship value, while 54.4% influenced by other factors not included in this the results. Keywords: Trust, Satisfaction, Relationship Value and Commitment.